The luminosity of the sun - Ashwell, Sophia; Barrett, Chris; Hatherly Paul; Hall, Adrian (The University of Hull)
An interactive screen experiment to measure the luminosity of the sun using a Bunsen oil spot photometer and a filament light bulb.